Fatwa Institutions and Digital Family Law: Online Marriage and Divorce in Indonesia (NU, Muhammadiyah, and MUI) - Zakaria, Muhammad Fadhlurrahman; Zubair, Zubair; Umar, Ihwan Setiawan (Mauriduna: Journal of Islamic Studies, 2025)
This research was important as it addressed the controversial issue of online marriage and divorce from an Islamic legal perspective, a topic that became increasingly relevant with the state's consideration of digitizing marital administration. The aim of this study was to analyze whether online marriage and divorce fulfilled the legal and religious requirements in Islam and how the three major Islamic institutions in Indonesia—Nahdlatul Ulama (NU), Muhammadiyah, and the Indonesian Ulema Council (MUI)—responded to this practice based on their respective methods of ijtihad. This research employed a qualitative method with a literature-based approach, analyzing fatwas, scholarly texts, and relevant legal sources. The findings revealed distinct differences in perspective: NU considered online marriage invalid due to non-fulfillment of essential conditions such as the requirement of being in one physical assembly, while Muhammadiyah allowed online marriage if all pillars and conditions were fulfilled, including uninterrupted ijab and qabul. MUI adopted a moderate stance, recognizing online marriage under specific conditions including government recognition. In terms of divorce, NU and MUI considered it valid outside the court under certain circumstances, whereas Muhammadiyah required it to go through the court system.